2022
DOI: 10.1002/ijc.34054
|View full text |Cite
|
Sign up to set email alerts
|

Now or later: Health impacts of delaying single‐dose HPV vaccine implementation in a high‐burden setting

Abstract: We aimed to quantify the health impact of immediate introduction of a single-dose human papillomavirus (HPV) vaccination program in a high-burden setting, as waiting until forthcoming trials are completed to implement single-dose HPV vaccination may result in health losses, particularly for cohorts who would age-out of vaccination eligibility. Two mathematical models fitted to a high-burden setting projected cervical cancer incidence rates associated with (a) immediate implementation of one-dose HPV vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Even with a pessimistic assumption that the efficacy of one dose is lower than two/three doses, adopting a one-dose schedule would free up vaccine doses to allow more rapid scale-up of vaccination, and generate the greatest cost savings and health gains with constrained supply in China. Our results about the one-dose schedule are generally consistent with previous modelling studies, 29 , 30 , 32 , 33 , 34 which suggest promising health benefits (in terms of improving both impact and efficiency) and favourable cost-effectiveness of one-dose strategies. However, few studies have explicitly incorporated supply constraints when comparing the impact of adopting a one-dose schedule with other strategies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Even with a pessimistic assumption that the efficacy of one dose is lower than two/three doses, adopting a one-dose schedule would free up vaccine doses to allow more rapid scale-up of vaccination, and generate the greatest cost savings and health gains with constrained supply in China. Our results about the one-dose schedule are generally consistent with previous modelling studies, 29 , 30 , 32 , 33 , 34 which suggest promising health benefits (in terms of improving both impact and efficiency) and favourable cost-effectiveness of one-dose strategies. However, few studies have explicitly incorporated supply constraints when comparing the impact of adopting a one-dose schedule with other strategies.…”
Section: Discussionsupporting
confidence: 90%
“… 28 Based on the low sexual activity and therefore low HPV prevalence among girls aged 9–14 years in China, our results suggest that constrained vaccine supplies should be prioritized to the older end of the 9–14 year old range. This is supported by several previous modelling studies based on other settings, 29 , 30 even for those have a relatively high proportion of who are sexually active at 14 years. Drolet and colleagues suggested that LMICs such as Nigeria and India (with 15%–25% of girls aged 14 years that are sexually active) could start with routine vaccination of 14-year-old females to achieve faster gains, and once supplies become available switch to routine vaccination at age of 9 years after a reverse MAC vaccination.…”
Section: Discussionsupporting
confidence: 85%
“…However, for many countries that do not yet offer HPV vaccination within national immunisation schedules (mostly LMICs, where the greatest cervical cancer burden occurs [5] ), the decision that must be made is whether to introduce one-dose or two-dose vaccination now, or whether to wait to introduce any vaccine. For those countries, modelling shows that the most detrimental scenario is to wait [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Three recent modelling studies have examined the potential population-level effectiveness of one-dose HPV vaccination in LMICs. 29 , 30 , 31 First, a comparative modelling study 29 that we did with colleagues from Harvard University, found that early implementation of one-dose routine vaccination of girls in Uganda would lead to greater health benefits than waiting 5 years until more information on vaccine efficacy is available from ongoing trials. The conclusion was robust across a range of revaccination mitigation scenarios.…”
Section: Discussionmentioning
confidence: 99%